Strategi Guru dalam Meningkatkan Minat Baca Siswa pada Pembelajaran Bahasa Indonesia di SDN 73/IX Simpang Sungai Duren - Putri Dwi Lestari; Tabroni Tabroni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the strategies used by teachers to increase students’ reading interest in the Indonesian language subject at SDN 73/IX Simpang Sungai Duren. The background of this research is the low reading interest among students, which negatively affects their comprehension and academic performance, particularly in Indonesian language learning. This study employed a qualitative approach using a case study method. Data were collected through classroom observations, interviews with teachers and students, and documentation of literacy-related activities. The results showed that teachers implemented several strategies to foster reading interest, including story-based learning, the use of visual and digital media, creative reading assignments, and a routine of reading before starting lessons. These strategies were proven to gradually increase students’ enthusiasm for reading and encouraged more active participation in learning. Supporting factors in the implementation of these strategies included the availability of engaging reading materials and support from the school administration. However, several inhibiting factors were also identified, such as the lack of adequate library facilities and students’ initially low reading motivation.This study concludes that the teacher's role is crucial in developing a reading culture at the elementary level. Therefore, it is recommended that schools provide ongoing professional development for teachers in literacy instruction strategies, and enhance literacy-supporting facilities to ensure the sustainable growth of students’ reading interest.